A new species of the genus Tithaeus from China (Arachnida: Laniatores: Epedanidae) - Lian, Wei-Guang; Zhu, Ming-Sheng; Kury, Adriano B. (Zootaxa, 2008)
The genus Tithaeus Thorell, 1891 is newly recorded from China with a new species: T. drac, based on specimens collected from Guangxi Province. The new record represents an expansion of 700 km to the northeast of the known range of the genus. The taxonomic status of the genus Tithaeus is discussed, based on external and male genital morphology.